Characterization of mammalian orthoreoviruses isolated from faeces of pigs in Zambia. (24th October 2020) - Harima, Hayato; Sasaki, Michihito; Kajihara, Masahiro; Gonzalez, Gabriel; Simulundu, Edgar; Bwalya, Eugene C.; Qiu, Yongjin; Okuya, Kosuke; Isono, Mao; Orba, Yasuko; Takada, Ayato; Hang'ombe, Bernard M.; et al.
Abstract : Mammalian orthoreovirus (MRV) has been identified in humans, livestock and wild animals; this wide host range allows individual MRV to transmit into multiple species. Although several interspecies transmission and genetic reassortment events of MRVs among humans, livestock and wildlife have been reported, the genetic diversity and geographic distribution of MRVs in Africa are poorly understood. In this study, we report the first isolation and characterization of MRVs circulating in a pig population in Zambia. In our screening, MRV genomes were detected in 19.7 % (29/147) of faecal samples collected from pigs by reverse transcription PCR. Three infectious MRV strains (MRV-85, MRV-96 and MRV-117) were successfully isolated, and their complete genomes were sequenced. Recombination analyses based on the complete genome sequences of the isolated MRVs demonstrated that MRV-96 shared the S3 segment with a different MRV isolated from bats, and that the L1 and M3 segments of MRV-117 originated from bat and human MRVs, respectively. Our results suggest that the isolated MRVs emerged through genetic reassortment events with interspecies transmission. Given the lack of information regarding MRVs in Africa, further surveillance of MRVs circulating among humans, domestic animals and wildlife is required to assess potential risk for humans and animals.